In Vitro evaluation of salt tolerance of poplars and willows - Khudolieieva, Lidiya; Kutsokon, Nataliya (ScienceRise: Biological Science, 2018)
The irrational anthropogenic influence on soils often leads to negative consequences, one of which is salinization. Among various types of salinity, chloride salinity has the greatest negative effect. Accumulatiоn of chlorine ions by plant cells causes disturbances in their metabolism, as a result of cell membrane damage. Such changes have a negative effect on the tree growth. Poplar and willow are energy trees with rapid growth and a wide range of adaptations to environmental conditions. These plants are not halophytes, but some genotypes are relatively salt-tolerant. Growing them in saline areas will have not only the ecological effect of soil remediation and importance for the urban horticulture, but can also bring economic profits, particularly in areas excluded from agricultural usage due to their salinity. The aim of the study was to analyze the salt tolerance of aspen (Populus tremula), hybrid poplar clone 'INRA 717-184' (P. tremula × P. alba) and willow clone 'Olympiyskiy vohon' (Salix alba × S. fragilis) under in vitro cultivation on the medium with sodium chloride added in concentrations 25 mM, 50 mM and 100 mM. General plant state, intensity of their growth (by the shoots’ length) and root formation (by number of roots) on the 10th, 30th and 60th day of cultivation were estimated. The results demonstrated that salt tolerance significantly varied in different genotypes. In hybrid poplar clone 'INRA 717-184', the intensity of growth activity was decreased after long-term cultivation under all investigated concentrations of sodium chloride. In aspen plants, a significant decrease of the intensity of shoots growth by 94.3 % compared to control was found only after two months of cultivation, then concentration of NaCl in media was 100 mM. The intensity of willow growth was not affected at any experimental treatment by sodium chloride. A statistically significant decrease of the intensity of root formation after the 1-st and 2-nd months of cultivation was shown only for aspen clones planted in the culture medium with 100 mM of sodium chloride added. In general, willow clones demonstrated higher intensity of root formation than poplar clones